Uso de rotas na área de uso e a relação com comportamento alimentar em Callithrix jacchus - Colombo, Audra Regina (2009)
Callithrix jacchus are small primates that live in cooperative reproductive family groups. They explore their home range in search of fruits, exudates and animal prey. In this study we investigate the existence of traveling routes and its relation with the feeding habits in a group of Callithrix jacchus. The group was followed for 6 months in an area of Atlantic secondary Forest at the FLONA-ICMBio of Nísia Floresta, Rio Grande do Norte. Two observers in alternated days collected data referring to the group s location using a GPS navigation device, plotting data in 5 minute intervals, and with a position accuracy under 9 meters. All behavioral recordings were done through focal time samplings. The recording windows were 15 minutes with 1 minute intervals. The main activity was foraging, which propelled the animals to explore the environment with inconsistent intensity through the months, and correlated with the location of fruits, exudates and sleeping sites. From another standpoint, most activities were focused in the core areas that featured most sleeping sites, exudates trees and fruit trees. Insects, mostly Orthopterans, were hunted in all areas. The greater ratio of movement was registered during the last hours of sunlight, when animals returned to the sleeping sites and ate a greater number of fruits. The spatial and seasonal distribution of fruits forced the animals to travel long routes. The capacity to remember the location and navigate efficiently through feeding sources is important to save energy and time costs. Learning and familiarizing with the environment through the use of landmarks and acquisition of new information is extremely important to increase the chances of survival in a constantly changing environment